Integrating Creative Problem-Solving in Electronic Teaching Materials to Enhance Problem-Solving Skills of High School Science Students - Mahardika, Andi Ichsan; Arifuddin, Muhammad; Lazuardi, Nana Sophia (FKIP Universitas Lampung, 2024)
Integrating Creative Problem-Solving in Electronic Teaching Materials to Enhance Problem-Solving Skills of High School Science Students. Objectives: The problem-solving ability of SMA Negeri 1 Amuntai students is still in the low category due to the unavailability of teaching materials that contain problem-solving skills. This research aims to produce electronic teaching materials using creative problem solving models on particle dynamics topics that are feasible to improve students' problem-solving skills. The specific purpose of this research is to describe the validity, practicality, and effectiveness of the electronic teaching materials developed. Methods: The research method used is a research and development method using the ADDIE model. The test subjects were 19 students of class X MIPA 1 SMAN 1 Amuntai. The research design used is one group pretest posttest. The data collection technique uses validity assessment instruments, questionnaires for the response of students and pretest-posttest learning outcome tests. Findings: The results showed: (1) electronic teaching materials are valid because their validity is 3.30 with valid categories, (2) teaching materials are practical because the response of students is 2.83 with practical categories, (3) electronic teaching materials are included as effective because the average n-gain score of 0.32 is in the effective category. Conclusion: Thus, electronic teaching materials using creative problem solving models on the topic of particle dynamics are worthy of use to improve students' problem-solving skills. Keywords: creative problem solving, electronic teaching materials, problem solving skills.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024147